2018
DOI: 10.1111/nph.15224
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic levels of nonstructural carbohydrates after 13 yr of drought and irrigation inPinus sylvestris

Abstract: Nonstructural carbohydrates (NSCs) are important for the growth and survival of trees. Drought may lead to a decrease in tree growth and to NSC depletion, whereas increased soil moisture in otherwise dry ecosystems may increase growth and NSC concentrations. A long-term (13 yr) irrigation experiment was conducted in a Pinus sylvestris-dominated forest located at the dry margin of the species in southern Switzerland. We measured the relative leaf area, growth, NSCs, needle δ C, [N] and [P] in trees on control a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 62 publications
(101 reference statements)
12
72
2
Order By: Relevance
“…These studies, along with recent evidence from the temperate zone (Schönbeck et al, ), suggest that NSCs may increase, even if only slightly, in response to seasonal drought in tropical forests. However, across sites, acclimation of leaf and plant traits such as height, leaf area, leaf mass per area, and stand density may allow homoeostatic mainentence of NSC concentrations; that is, they maintain relatively stable values despite long‐term environmental variation (see, e.g., homoeostasis of NSCs, e.g., Rowland et al, ; leaf gas exchange, e.g., Ehleringer & Cerling, , McDowell et al, ; or temperature, e.g., Michaletz et al, , , Blonder & Michaletz, ).…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…These studies, along with recent evidence from the temperate zone (Schönbeck et al, ), suggest that NSCs may increase, even if only slightly, in response to seasonal drought in tropical forests. However, across sites, acclimation of leaf and plant traits such as height, leaf area, leaf mass per area, and stand density may allow homoeostatic mainentence of NSC concentrations; that is, they maintain relatively stable values despite long‐term environmental variation (see, e.g., homoeostasis of NSCs, e.g., Rowland et al, ; leaf gas exchange, e.g., Ehleringer & Cerling, , McDowell et al, ; or temperature, e.g., Michaletz et al, , , Blonder & Michaletz, ).…”
Section: Introductionsupporting
confidence: 52%
“…This result is consistent with previous studies in which NSC concentrations have been found to be relatively resistant to change under all but the most extreme conditions. Variation in temperature and moisture have been shown to have modest impacts on NSC concentrations over seasonal (Martínez‐Vilalta et al, ) and decadal timescales (Rowland et al, ; Schönbeck et al, ), with only the most severe conditions that result in plant death causing larger NSC declines (Adams et al, ). The mechanisms driving such homoeostatic balance of NSCs against large changes in short‐ and long‐term precipitation are unknown, but include shifts in NSC consumption, for example, to growth, defence, and energy production, that match any shifts in photosynthesis during drought (McDowell, ).…”
Section: Discussionmentioning
confidence: 99%
“…δ 13 C analysis was used to identify different PM following O'Leary (). The leaf sugar pool size (i.e, [Sugars]) at the end of fog exposure was photometrically determined following the protocol of Schönbeck et al ().…”
Section: Methodsmentioning
confidence: 99%
“…The leaf sugar pool size (i.e, [Sugars]) at the end of fog exposure was photometrically determined following the protocol ofSchönbeck et al (2018).…”
mentioning
confidence: 99%
“…The irrigation treatment in the Pfynwald experiment added c. 500-600 mm water per year. This doubling of the natural precipitation increased stem radial growth, leaf area, needle and shoot lengths, whereas crown transparency decreased (Dobbertin et al, 2010;Eilmann et al, 2013;Sch€ onbeck et al, 2018). Furthermore, the irrigated trees adjusted their root production to the irrigation in terms of a significantly increased fine-root biomass (Brunner et al, 2009;2019;Herzog et al, 2014).…”
Section: Introductionmentioning
confidence: 99%